Pedampingan Kasus Migrant Care dalam Mengatasi Kasus Human Trafficking yang Terjebak Online Scammer: Perspektif Kesejahteraan Sosial - Kinanti Putri Herlambang; Wa Ode Asmawati (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Migrant workers are vulnerable to exploitation due to transnational and well-organized global human trafficking networks. Recently, a new modus operandi has emerged in human trafficking cases, namely recruitment under the pretext of employment in the overseas digital industry, promoted through social media and LinkedIn. Although these offers appear promising, they instead entrap migrant workers in trafficking schemes. Therefore, comprehensive case assistance involving the roles of government institutions and non-governmental organizations is urgently needed to protect victims. This study aims to examine the case assistance provided by Migrant CARE in addressing human trafficking cases in which victims are trapped as online scammers, viewed from a social welfare perspective. This research employs a descriptive qualitative approach through observation, interviews, and documentation. The findings indicate that the social interventions carried out by Migrant CARE are effective from the engagement stage through the follow-up stage. Supporting factors in the success of case assistance include proactive involvement from the government, victims, families, and the media. Meanwhile, inhibiting factors include the absence of personal documents such as passports, identity cards, and family cards, confiscation of mobile phones, and cross-national conflicts. From the individual perspective, supporting factors consist of personal resilience, courage, motivation, and skills, whereas inhibiting factors include victims’ hesitation to leave human trafficking situations due to fear of the risks involved.